IMPLEMENTATION OF PROBLEM BASED LEARNING WITH AUDIO VISUAL TO IMPROVE CRITICAL THINGKING AND LEARNING OUTCOMES OF HISTORICAL SUBJECTS - ririt nur erlina; mohammad na'im; Rully Putri Nirmala Puji (History Education, University of Jember, 2020)
Abstract Historical learning has skills that are able to develop a level of critical thinking. Based on the thinking about learning in class XI IPS 3 Cluring 1 Public High School has a low level of critical thinking skills, with discussion: (1) the material delivered is monotonous; (2) more than 50% of students are only able to answer questions in a low cognitive domain; (3) the media used in learning still use conventional media. The results showed a percentage of the increase in critical thinking skills, as follows: (1) focusing questions in cycle 1 of 51.47%, cycle 2 of 64.70%, cycle 3 of 76.47%; (2) analyzing arguments in cycle 1 by 50%, cycle 2 by 61.02%, cycle 3 by 70.58%; (3) asking and answering in cycle 1 is 52.20%, cycle 2 is 62.25%, cycle 3 is 71.32%; (4) estimation of source credibility in cycle 1 is 54.41%, cycle 2 is 60.29%, cycle 3 is 78.67%; (5) rounds and consideration of the first discussion cycle of 48.52%, cycle 2 was 66.17%, cycle 3 was 77.94%; (6) evaluation of the results of the discussion in cycle 1 was 48.52%, cycle 2 was 62.50%, cycle 3 was 71.32%; (7) consider the results of cycle 1 of 55.14%, cycle 2 of 66.17%, cycle 3 of 77.94%; (8) make cycle 1 61.76%, cycle 2 72.79%, cycle 3 77.20; (9) the term transition in cycle 1 is 50%, cycle 2 is 58.82%, cycle 3 is 77.20%; (10) Cycle thinking in cycle 1 is 53.67%, cycle 2 is 63.23%, cycle 3 is 70.58%; (11) determine the cycle in cycle 1 of 52.47%, cycle 2 is 64.70%, cycle 3 is 72.05%; (12) cycle with other people in the first cycle of 59.55%, cycle 2 was 64.47%, cycle 3 was 83.83%. learning outcomes obtained on average in cycle 1 were 73.08, cycle 2 was 75.73 and cycle 3 was 76.17.